Levetiracetam monotherapy for treatment of structural epilepsy in dogs: 19 cases (2010–2015). (14th October 2017) - Kelly, Darren; Raimondi, Francesca; Shihab, Nadia
Abstract : To evaluate the efficacy and tolerability of levetiracetam monotherapy in dogs with structural epilepsy. Retrospective case series. Nineteen client‐owned dogs with structural epilepsy. Seizure frequencies after initiation of treatment were used to evaluate the efficacy of levetiracetam monotherapy. Seizure control was considered good if no seizures occurred within three months of starting treatment or poor if seizures returned within one month of starting treatment. Tolerability was evaluated by considering the occurrence and severity of any reported side effects. Ten of the 19 dogs were considered to have a good response to treatment with 7 achieving complete seizure freedom. Nine dogs were considered to have poor response to treatment. There was a statistically significant reduction in the percentage of patients experiencing cluster seizures from 68.4% to 15.8% (p=0.002). Side effects were noted in 8 of the 19 dogs but were considered mild in all cases. Follow‐up times ranged from 12 days to 426 days. When used in conjunction with other appropriate therapies, levetiracetam may be an efficacious option for monotherapy in dogs with structural epilepsy. Its tolerability makes it a suitable option for use in a wide variety of patients.